Students’ Perception Toward E-Learning in Pandemic Era at English Education Study Program of IAI Muhammadiyah Sinjai - Harmilawati, Harmilawati; Khaerunnisa, Khaerunnisa (JLE: Journal of Literate of English Education Study Program, 2020)
This research aims to know the problem of what is the students’ perception toward E-Learning at English Education Study Program of IAI Muhammadiyah Sinjai, especially during the pandemic era. The researchers use the descriptive qualitative method in this research. The population in this research were all students in English Education Study Program, Academic Year 2017/2018 of Faculty Tarbiyah and Teacher Training, IAI Muhammadiyah Sinjai that consist of 34 people. While the sample of this research is also 34 people by using Total Sampling technique. Technique of collection data that used in this research were interview, coding, classifying, and documentation. The result of this research showed that most of the students thought that the use of E-Learning in pandemic era was negative perceptions. These negative perception caused by some reasons, namely: the limitation of network and internet quotes; unsupportive facilities, such as laptop and gadget or handphone; limited time in interacting with lecturers.